EFFICACY OF RASON, ASHWAGANDHA AND ASHWATHA IN DIABETIC ERECTILE DYSFUNCTION - A CRITICAL REVIEW - Soni, Pradeeep; Sharma, P.L. (International Journal of Ayurveda and Pharma Research, 2017)
Background: Erectile dysfunction (ED) is a common condition among men with diabetes and it is associated with reduced quality of life among those affected. ED has reported to increase with age, increasing from 5% at 40 years to > 50 % at 75 years of age. The incidence of ED is increasing day by day with the incidence of diabetes and the prevalence of ED is estimated between 35-50%. Erectile Dysfunction (ED); inability to achieve and/or maintaining an erection sufficient to permit satisfactory sexual intercourse, is one of complication associated with diabetes and often ignored. ED problem is psycho-organic, because it affects the man as whole. The diabetes and oxidative stress are major contributors for ED. Objective: Though there are many medicinal plants shows the antidiabetic and related to beneficial effect in ED. Among those medicinal plants we selected and reviewed Rason (Allium sativum Linn.), Ashwagandha (Withania somnifera Dunal) and Ashwatha (Ficus religiosa Linn.) To assess and find out the antidiabetic effect and their efficacy in ED. Research methods and procedure: In the present study, we collected and compiled (Various research journals) the references regarding previous work done on antidiabetic effect of above mentioned medicinal plants w.s.r to E.D. Discussion & Conclusion: on the basis of our literary review it is concluded that the Rason (Allium sativum), Ashwagandha (Withania somnifera) and Ashwatha (Ficus religiosa) are responsible for significant antidiabetic effect with the hypoglycemic property and also exhibit the efficacy in ED due to aphrodisiac properties.